The law of sovereign wealth funds - Bassan, Fabio (Cheltenham, UK : Edward Elgar, 2011)
This book provides a definition and classification for Sovereign Wealth Funds (SWFs) and discusses its phenomenon within the legal context. It identifies the rules applicable to SWFs and focuses on the bilateral relationships between states. In eight extensive chapters, Fabio Bassan considers whether SWFs may enjoy immunity with respect to host state measures as well as protection in Bilateral Investment Treaties Written from an international law perspective, The Law of Sovereign Wealth Funds will appeal to students of international business, international organizations, banks and governments.
Includes bibliographical references (p. 157-167) and index.
Keywords: Sovereign wealth funds -- Law and legislation; Investments, Foreign -- Law and legislation